On the history of a subterranean geopolitics - Klinke, I (Elsevier, 2019)
Geopolitics has in recent years been framed as a flat discourse whose cartographic obsessions prevent it from appreciating both the vertical dimension in which statecraft and armed conflict operate as well as the earth’s geologic agency. This assessment, I argue, is based on an incomplete reading of the geopolitical tradition. A journey through the history of geopolitics reveals that whilst thinkers like Alfred Mahan, Halford Mackinder and Carl Schmitt displayed a tendency for flat earth thinking, it was the German political geographer Friedrich Ratzel (1844–1904) who developed a rich tapestry of terms to theorise the power and politics of geology and the underground. The advent of large scale conventional and later nuclear bombing in the 1940s prompted geopoliticians on both sides of the Atlantic to become increasingly interested in the 3-dimensionality of the struggle for space. This paper suggests the need for a dialogue between the intellectual history of geopolitics and the growing literatures on geopower and vertical geopolitics.